Caracterização dos empreendimentos e perfil dos empreendedores do centro comercial de São Pedro do Potengi - RN - Medeiros, Marcelo Miguel Moura de (Universidade Federal Rural do Semi-Árido, 2018)
Entrepreneurship is essential for the creation and growth of a country’s business, as it generates Jobs and, causes the capital turn into society by improving the quality of life of the population. Has been taking great shape in Brazil and, consequently, in Rio Grande do Norte. Based on this information, this work sought to carry out na investigation to characterize the entrepreneurs profile of the cities of this sates. In view of this information the work of conclusion of the course was done in the city of São Pedro do Potengi where he sought to know the shopping center, thus making us have a survey of profiles of entrepreneurs and the current scenario in which the city is when it comes to the economy. We carried out a field survey in which a questionaire was applied to the owners of the companies, where the necessary data and information were collected. Through the analysis of data it was noticed that in the comercial center of the city of São Pedro do Potengi – RN the majority of the entrepreneurs is male between na age group of 30 to 50 years old, most of the enterprises make use of Technologies to optimize their time, it was noticed that about 85% of the companies visited are from the commercial area. It was verified that the municipality of São Pedro do Potengi – RN presents some déficits and difficulties and with this it is noticed that the municipality needs investment in industrial areas in order to reduce the rate of unemployment of the city, to increase the capital moviment.
Monografia
Keywords: Empreendimentos; Empreendedores; Empreendedorismo; São Pedro do Potengi-RN; Businesses; Entrepreneurs; Entrepreneurship; São Pedro do Potengi; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA